SPATIAL VARIABILITY OF SOIL ACIDITY FACTORS ON DIFFERENT MANAGEMENT SYSTEMS - SOUZA, LUCIANO DA SILVA (1999)
Soil spatial variability of acidity factors (pH, Ca, Mg, Ca+Mg, AI, H+Al, sum of bases, cation exchangecapacity, and bases saturation) was studied in different soils and management systems, at two regions of Rio Grande do Sul -Brazil a) Eldorado do Sul, on a dark red podzolic soil, Kandiudult (conventional tillage, no-tillage, and chisel plow, in plots ofa soil management trial, and pasture), using a grid sampling of 1 x 1 m at the depths of 0-0,05 and 0,05-0,20 m; b) Passo Fundo,on a dusky red latosol, Hapludox (conventional tillage and no-tillage), and a dark red latosol, Hapludox (pasture), in agriculturalfarms, using a grid sampling of 10 x 10 m at the depths of 0-0,10, 0,10-0,20, and 0,20-0,30 m. Wheat yield variability wasstudied only in Passo Fundo by harvesting areas of 1 m 2 , at the same grid sampling. Soil properties followed a normaldistribution, in most of management systems and dephts. The lowest variability, evaluated by coefficients of variation, wasfound for pH and cation exchange capacity (CVs<10%), and the highest for Al (CVs>40%), with other properties placingintermediary position (10%<CV5 <40%). Among cultivated areas, no-tillage exhibited greater coefficients of variation, followedby minimum tillage and conventional tillage. Spatial correlation was found for pH, H+Al, and bases saturation in Eldorado doSul, whereas in Passo Fundo was found for all soil properties (with exception to H+Al and cation exchange capacity, inpasture) and for wheat yield on the management systems studied. No-tillage exhibited positive cross-correlation for wheatyield with Ca, with Mg, with Ca+Mg, with sum of bases, and with cation exchange capacity.